Penerapan Metode Extreme Programming menggunakan Framework Laravel dalam Pengembangan Sistem Informasi Khazaregsys - Nuurussa'aadah, Fathimah; Maulana, Reza; Wiyono, Bambang Harie (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
This study is intended to solve the problem of parents of prospective students who need more information about PPDB and the occurrence of repetition in the data collection of prospective students who have registered by the committee due to duplicate data. This study is included in the Research and Development research type, which aims to develop a web-based PPDB information system (Khazaregsys) at SDIT Kharisma Az-Zahra, which helps increase the efficiency and transparency of the PPDB process. In its development, the method used is Extreme Programming, which uses the Laravel framework and MySQL as a database server. This study's data was obtained using various methods, such as literature studies, observations, questionnaires, and interviews. The data will be analyzed using the mixed method with the majority of qualitative analysis, namely from the interviews, observations, and literature studies, as well as quantitative analysis of the questionnaire results. Testing of the system that has been developed will involve black box testing to test all features in the system with a particular focus on the prospective student registration system and usability testing through user acceptance testing (UAT) to measure the system's effectiveness from the user's perspective. Khazaregsys has been proven to have a good level of effectiveness, which is supported by the test results, which obtained a score of 62%, meaning "Agree" from the parent's point of view, and 64.5%, meaning "Agree" from the school teacher's point of view.